The clinical neurophysiology primer - Blum, Andrew S.; Rutkove, Seward B. (Totowa, New Jersey : Humana Press, 2007)
Presents a broad yet focused treatment of central topics in the field of clinical neurophysiology. This volumen was inspired by the clinical neurophysiology lectura series at Beth Israel Deaconess Medical Center ant Rhode Island Hospital, where faculty and trainees at these renowned teaching hospitals participate in a lectura series over the course of the academic year.
I. Basic considerations II. Electroecephalography III. Nerve conduction studies and electromyography IV. Autonomic testing, evoked potentials, and sleep
Includes index
Keywords: NEUROPSICOLOGIA; NEUROPHYSIOLOGY; FISIOLOGÍA DEL SISTEMA NERVIOSO